Sexuality, Subjectivity, and Motherhood in Mengestu’s The Beautiful Things That Heaven Bears (2007) - Truye, Bekelech; Yazbec, Olga (NOBEL: Journal of Literature and Language Teaching, 2024)
This article aims to explore the representation of the female protagonist’s subjectivity and sexuality in Dinaw Mengestu’s novel The Beautiful Things That Heaven Bears (2007). This novel has been analyzed from other critical perspectives. However, a post-structural feminist analysis of this novel can shed light on the female character’s subjectivity and sexuality, as well as our understanding of womanhood in general. The researchers discovered that the female character in the selected novel is modeled as a person who resists the exclusion of women from knowledge and power in a patriarchal society. She represents a new generation of women who struggle against the subjugation of women. Besides, she resists submissiveness to negative experiences in sexuality. In a nutshell, she is made visible through resilience.